Redefining Classroom Management in Hybrid Education Setting from the Perspectives of EFL and German Language Instructors - Mehmet Doğan; Mehmet Saraç (International Journal of Asian Education, 2022)
This study aimed to investigate the perceptions of English and German language instructors regarding the opportunities and challenges for classroom management created by the hybrid education setting. The participant group included 21 instructors (17 EFL and 4 German). Participating instructors were employed at the School of Foreign Languages, and they were actively teaching in the hybrid education model developed by the school. A convenient sampling strategy was adopted while determining the participants. The study adopted a qualitative research design, and the data was collected through semi-structured interviews. The qualitative data was analyzed by following the content analysis procedures. The findings were presented through the emerging codes and themes. The results showed that the participating instructors faced varying challenges in terms of classroom management in the online classes. The study findings revealed a good deal of research evidence on the divergent training needs of instructors because the instructors found it hard to implement their traditional classroom management strategies in online classes. Planners and policymakers are provided insights for setting clear responsibilities and rules for learners during the online courses and providing in-service training opportunities for instructors as the new conditions call for innovative strategies to implement effective classroom management practices to contribute empirically, contextually, and policy.